Rapid self-driven anti-icing material and preparation method thereof

Through the synergistic effect of modulus mismatch structure and microstructure, the problem of existing anti-icing materials failing in low temperature and high humidity environments is solved, and large-area rapid deicing and excellent anti-icing performance are achieved, which is suitable for a variety of ice formations. environment.

CN119242266APending Publication Date: 2025-01-03UESTC (SHENZHEN) ADVANCED RES INST +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411345048.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing superhydrophobic anti-icing materials fail in low temperature and high humidity environments, and cannot quickly and thoroughly remove ice deposits, and have low mechanical properties, which affects durability.

Method used

Anti-icing materials that use modulus mismatch structure and microstructure synergistically interact, through the combination of high-modulus and low-modulus materials, form a modulus fracture type along the Z-axis direction, and combine microstructures with micro- or nanoscale to achieve ice. -Fast interface cavitation quickly.

Benefits of technology

It realizes fast, energy-consuming deicing in large areas, maintains excellent anti-icing performance, has high efficiency, durability and a variety of regulatory factors, and is suitable for different icing environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242266A_ABST
    Figure CN119242266A_ABST
Patent Text Reader

Abstract

The invention provides a rapid self-driven anti-icing material and a preparation method thereof. The rapid self-driven anti-icing material comprises a modulus span formed by at least two materials, a Z-axis perpendicular to a substrate direction, and an upper'hard (high-modulus material) 'structure and a lower'soft (low-modulus material)' structure distributed along the Z-axis direction, the surface of the large-area rapid self-driven anti-icing material is provided with a microstructure (micron-scale or nano-scale, continuous or discontinuous, isotropic or anisotropic wrinkles, micro-columns, grooves, inverted triangular bulges and the like). And the surface has an isotropic continuous wrinkle structure (figures), and has modulus span (hard at the upper part and soft at the lower part) in the Z-axis direction. The material can realize zero-energy-consumption deicing (only under the action of self gravity of ice deposits or wind power) without depending on a lubricating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-icing materials, and in particular to a fast self-driving anti-icing material and a preparation method thereof. Background Art

[0002] The problem of ice formation on surfaces in low-temperature environments is widely involved in important industrial fields such as railway transportation, aerospace, wind power and photovoltaic power generation, and communications, causing serious harm to human social production and life. Surface ice will not only reduce the operating performance and efficiency of equipment or devices, but also threaten people's lives and property safety in serious cases. Considering the comprehensive factors of energy, manpower, and environment, anti-icing methods that do not require energy consumption and spontaneously remove ice (i.e., passive anti-icing) have attracted widespread attention from researchers.

[0003] Anti-icing surfaces and super-slip anti-icing materials with super-hydrophobic structures have been vigorously developed. Anti-icing materials with super-slip surfaces are usually formed by physically or chemically (coating or grafting) on ​​the surface of the base material to give it a lubricating layer with good fluidity, thereby reducing the ice adhesion strength. However, no matter how the lubricating layer is formed, problems such as the lubricating layer being exhausted or dust adhering to the surface cannot be avoided. Super-hydrophobic surfaces with complex structures can show good anti-icing performance under certain specific experimental conditions. However, when the super-hydrophobic structure surface is placed in a low temperature and high humidity environment for a long time, its structure will lose its characteristics due to condensation.

[0004] Reducing the modulus of the material is an effective way to reduce the ice adhesion strength. However, when removing ice from a low modulus surface, stick-slip motion will occur because the ice-solid interface cannot be completely and quickly broken. That is, the ice continues to slide on the surface of the material along the direction of the applied force, and there is cavitation propagation (Schallamach waves) at the ice-solid interface. The sliding of ice deposits does not guarantee that the ice deposits can be quickly and completely detached from the surface (that is, complete interface cavitation), which will cause more energy consumption and is not conducive to large-scale deicing. On the other hand, a too low modulus makes the mechanical properties of the material lower, which is not conducive to the durability of the material.

[0005] Therefore, combining low ice adhesion strength with rapid interfacial cavitation (the ice-material interface is completely replaced by air) becomes a key characteristic for achieving rapid deicing over a large area. Summary of the invention

[0006] In response to the above-mentioned problems in the prior art, the present application proposes a fast self-driving anti-icing material and a preparation method, including a modulus mismatch structure formed by at least two materials, the modulus span of the modulus mismatch structure is along the Z-axis direction or at a certain angle to the Z-axis; the surface of the fast self-driving anti-icing material has a microstructure, and the modulus mismatch structure and the surface microstructure have a synergistic effect.

[0007] Preferably, the modulus mismatch structure is a structure of high modulus material and low modulus material distributed along the Z-axis direction.

[0008] Preferably, the microstructure is micrometer-scale or nanometer-scale, continuous or discontinuous, isotropic or anisotropic folds, micropillars, grooves, fish-scale protrusions, inverted pyramids or inverted triangle protrusions.

[0009] Preferably, the modulus mismatch structure comprises a first modulus material and a second modulus material, and the elastic modulus of the first modulus material and the elastic modulus of the second modulus material are not equal, thereby forming a modulus fracture mutation of the first modulus material and the second modulus material in a certain direction.

[0010] Preferably, the difference between the elastic modulus of the first modulus material and the elastic modulus of the second modulus material is in the range of 0.04 MPa-3.6 GPa.

[0011] Preferably, the first modulus material is a metal or metal oxide material, glass, a silicon substrate or a high molecular polymer organic material.

[0012] A method for preparing a fast self-driving anti-icing material comprises the following steps:

[0013] Step 1: preparing a substrate sheet or film material of a first modulus material, and preparing the substrate sheet or film material by spin coating, spray coating, casting, film laying, or roller coating the first modulus material with a lower modulus;

[0014] Step 2: Prepare a second modulus material with a higher modulus in a manner that can cause thermal instability in the first modulus material; since the first modulus material is instability and deforms, when the applied conditions are removed, the two shrinkage mismatches due to different moduli lead to surface microstructures.

[0015] Preferably, step 1 comprises:

[0016] Step 11A: Making a template with a microstructure according to the designed pattern;

[0017] Step 12A: injecting a precursor of the first modulus material into the mold, and forming a first modulus material substrate with a microstructure after curing and demoulding.

[0018] Preferably, step 2 further comprises: step 21: covering the second modulus material on the first modulus material substrate by deposition, spraying or film laying.

[0019] Preferably, step 1 further comprises:

[0020] Step 11B: Making a template with a microstructure according to the designed pattern;

[0021] Step 12B: forming a microstructure on the first modulus material film by hot embossing.

[0022] The above technical features can be combined in various suitable ways or replaced by equivalent technical features as long as the purpose of the present invention can be achieved.

[0023] The fast self-driving anti-icing material and preparation method provided by the present invention have at least the following beneficial effects compared with the prior art:

[0024] 1. The self-driving anti-icing material of the present invention, which can realize large-area rapid deicing, can remove ice deposits with zero energy consumption under the action of ice gravity or wind force;

[0025] 2. The self-driving anti-icing material capable of realizing large-area rapid deicing of the present invention can completely remove ice deposits from a large area in a short time;

[0026] 3. The self-driving anti-icing material of the present invention that can realize large-area rapid deicing has excellent and long-lasting anti-icing performance based on its properties (not relying on lubricants);

[0027] 4. The method for preparing the self-driven anti-icing material capable of realizing large-area rapid deicing of the present invention is quick and simple, has a wide range of selectable raw materials, and can realize large-scale production;

[0028] 5. The self-driving anti-icing material of the present invention that can achieve large-area rapid deicing has multiple adjustable factors and can meet the needs of different application scenarios.

[0029] 6. The self-driving anti-icing material of the present invention that can achieve large-area rapid deicing can maintain excellent anti-icing performance under a variety of icing environments (icing mode, temperature, humidity, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein:

[0031] Figure 1 It is a schematic diagram of a self-driven anti-icing material of the present invention, which has an isotropic continuous fold structure on the surface and a modulus span in the Z-axis direction ("hard" on the top and "soft" on the bottom);

[0032] Figure 2 This is a schematic diagram of an exemplary method for preparing a self-driving anti-icing material capable of realizing large-area rapid deicing according to the present invention;

[0033] Figure 3 It is a schematic diagram of another exemplary method for preparing a self-driving anti-icing material capable of realizing large-area rapid deicing according to the present invention;

[0034] Figure 4It is a schematic diagram of another exemplary method for preparing a self-driving anti-icing material capable of realizing large-area rapid deicing according to the present invention;

[0035] Figure 5 Diagram of the experimental setup for testing ice adhesion;

[0036] Figure 6 The deicing curves of the high modulus surface, the low modulus surface, the modulus mismatch surface and the modulus mismatch-microstructure surface are compared in Example 5. The results show that the modulus mismatch-microstructure surface has a low ice adhesion strength of less than 10 kPa.

[0037] Figure 7 The ice adhesion strength results of the modulus mismatch-microstructure surface and the low modulus surface with and without microstructures are compared in Example 8. The results show that a single microstructure cannot achieve a reduction in adhesion strength. There is a synergistic effect between the modulus mismatch and the microstructure.

[0038] Figure 8 The changes in ice adhesion strength of a series of self-actuated anti-icing materials with the same thickness of the top layer of Parylene and different modulus of the bottom layer of PDMS in Example 9 are compared with the surface of the same composition with only the modulus mismatch structure. The results show that the modulus has an effect on the adhesion strength of the material, as well as the synergistic effect of modulus mismatch and microstructure.

[0039] Fig. 9 The thickness of the parylene layer corresponding to different parylene contents in Example 10;

[0040] Fig.10 In Example 10, the ice adhesion strength of a series of self-actuated anti-icing materials with different parylene thicknesses and the same modulus PDMS bottom layer was tested. The results show that the thickness of the high modulus layer has an effect on the ice adhesion strength.

[0041] Fig.11 This is a demonstration of gravity self-desorption of 19*19cm ice on the surface of the self-driven anti-icing material (modulus mismatch-microstructure) and low modulus material in Example 11. The results show that the self-driven anti-icing material can automatically remove ice on its surface under the driving effect of gravity.

[0042] Fig.12 In Example 12, the surface of the 1*0.7m large-area self-driven anti-icing material (modulus mismatch-microstructure) automatically removes ice (0.9*0.6m) on the surface under the action of gravity.

[0043] Fig.13 The figure is a comparison of the intrinsic ice adhesion strength of the self-actuated anti-icing material (modulus mismatch-microstructure) and the material of different system materials in Example 16. The results show that the design principle of the self-actuated anti-icing material is universal.

[0044] Fig.14 The change in ice adhesion strength of the self-driven anti-icing material (modulus mismatch-microstructure) after 100 cycles of deicing in Example 17. The results show that the material has good durability.

[0045] Fig.15 The ice adhesion strength of the self-actuated anti-icing material (modulus mismatch-microstructure) under five different icing conditions in Example 18. The results show that the material can be applied to different icing conditions.

[0046] Fig.16 These are the experimental conditions in the icing wind tunnel in Example 18.

[0047] Fig.17 The ice adhesion strength of the self-actuated anti-icing material (modulus mismatch-microstructure) at different icing temperatures in Example 19. The results show that the icing temperature has little effect on the anti-icing performance of the material.

[0048] Fig.18 This is a self-cleaning demonstration of the self-actuated anti-icing material (modulus mismatch-microstructure) and super-slippery surface in Example 21. The results show that the self-actuated anti-icing material has self-cleaning properties.

[0049] Fig.19 The changes in ice adhesion strength of three self-driven anti-icing materials (modulus mismatch-microstructure) after 31 days of salt spray test in Example 22. The results show that this series of materials has good salt spray resistance.

[0050] Fig. 20 The change in ice adhesion strength of the self-driven anti-icing material (modulus mismatch-microstructure) after 30 days of UV aging test in Example 23. The results show that this series of materials has good UV resistance.

[0051] Fig.21 The change in ice adhesion strength of the self-driven anti-icing material (modulus mismatch-microstructure) in Example 24 after 50 times of 3M tape tearing test. The results show that this series of materials have good mechanical properties. DETAILED DESCRIPTION

[0052] The present invention will be further described below in conjunction with the accompanying drawings.

[0053] like Figure 1The self-driving anti-icing material provided by the present invention that can realize large-area rapid deicing has at least two materials with different moduli that form a fracture modulus change in the direction perpendicular to the anti-icing surface (Z axis); the surface of the material has a microstructure of a certain scale (micrometer scale or nanometer scale, continuous or discontinuous, isotropic or anisotropic wrinkles, micropillars, grooves, inverted triangular protrusions, etc.). Taking the Z-axis direction as an example, on the one hand, due to the existence of modulus mismatch, the apparent elastic modulus (E*) of the entire material is relatively low (close to the low modulus layer), and the high modulus layer is in direct contact with the ice to form a rigid interface, avoiding the generation of dynamic stick-slip motion, so that the interface cavitation time is reduced. And because materials with different moduli have different deformation capabilities, when external forces (gravity, wind, etc.) are applied, special deformations will occur on the material surface, which further promotes the generation of cracks. On the other hand, the existence of microstructures will further increase the number of cracks, further weakening the bonding strength of the ice-material interface, achieving complete shedding of ice (achieving complete interface cavitation), and creating basic conditions for rapid de-icing over a large area.

[0054] Preparation method of self-driving anti-icing material capable of realizing large-area rapid deicing:

[0055] The self-driving anti-icing coating material of the present invention that can achieve large-area rapid deicing can be made by a variety of methods and can be obtained by regulating factors such as the degree of modulus mismatch (difference in elastic modulus between raw materials, material content, thickness, etc.), surface microstructure characteristics (microstructure shape, depth, frequency, anisotropy / isotropy, continuity, etc.), and surface chemical properties.

[0056] The following uses PDMS (polydimethylsiloxane) and parylene as examples to provide several optional methods. The preparation process of other basic materials can be followed accordingly.

[0057] Preparation method 1: Interface instability method

[0058] This method is suitable for use when the substrate material has the characteristic of interface instability.

[0059] Step 1: Solidify the first modulus material on the substrate to obtain the first modulus material base 21 (eg Figure 2 shown).

[0060] Step 2: Deposit the second modulus material on its surface by vacuum coating. Since the first modulus material expands under coating conditions (high temperature), when the conditions are unloaded, the modulus difference between the first modulus material and the second modulus material causes mismatched deformation, forming a surface of the second modulus material 22 with microstructures. The difference in modulus between the two causes mismatched shrinkage, resulting in surface microstructures.

[0061] Preparation method 2: replica method

[0062] This method is suitable for use when the substrate material does not have the characteristics of interface instability.

[0063] Step 1: Design a modulus pattern and process a template 31 (such as Figure 3 There is no limitation on the specific processing method. A common processing method is to transfer the pattern on the photomask to a substrate coated with photoresist by exposure to form a template with a three-dimensional structure.

[0064] Step 2: Reversely replicate the three-dimensional structure on the template 31 with PDMS, a first modulus material, and demould to obtain a first modulus material substrate 32 complementary to the template pattern.

[0065] Step 3: Cover the second modulus material 33 on the surface of the first modulus material substrate 32 by vacuum coating, spraying, film laying, etc.

[0066] Preparation method 3: Imprinting method

[0067] Step 1: Design a modulus pattern and process a template 41 (such as Figure 4 There is no limitation on the specific processing method. A common processing method is to transfer the pattern on the photomask to a substrate coated with photoresist by exposure to form a template with a three-dimensional structure.

[0068] Step 2: Using the template 41 as a mold, reversely replicate its three-dimensional structure on the first modulus material by (heating) embossing, demoulding, and obtaining a first modulus material substrate 42 complementary to the template pattern

[0069] Step 3: Cover the second modulus material 43 on the surface of the first modulus material substrate 42 by vacuum coating, spraying, film laying, etc.

[0070] Adjustment factors that can achieve rapid de-icing over a large area:

[0071] According to the needs of practical applications, the self-driving anti-icing material capable of large-area rapid deicing of the present invention can adjust the performance through various factors, including the degree of modulus mismatch (elastic modulus difference between raw materials, material content, thickness, etc.), surface microstructure characteristics (microstructure shape, depth, frequency, anisotropy / isotropy, etc.), surface chemical properties, etc., so as to achieve the performance adjustment of the self-driving anti-icing material capable of large-area rapid deicing.

[0072] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present disclosure and should not be regarded as limiting the scope of this patent. The PDMS used in the following examples is Sylgard 184 silicone elastomer base, Sylgard 184 silicone elastomer curing agent, and parylene produced in the United States. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer.

[0073] Example 1

[0074] The precursor was prepared by mixing the PDMS monomer and the curing agent in a ratio of 5:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, and 80:1, and then placed in a vacuum oven after being stirred evenly to remove bubbles at room temperature. The precursor was poured onto an aluminum plate with a flat bottom (the thickness was controlled by a silicone plate), cured at 100°C for 12 hours, and stored.

[0075] Example 2

[0076] The sample in Example 1 was placed in a vacuum coating apparatus, 1.5 g of parylene was added, and the coating was carried out under vacuum conditions. After the coating was completed, the sample was taken out and stored. (The sample with a microstructure on the surface was obtained, i.e., a self-driven anti-icing material)

[0077] Example 3

[0078] Place the glass slide in a vacuum coating apparatus, add 1.5 g of parylene, and coat the slide under vacuum conditions. After coating, remove the slide and store it.

[0079] Example 4

[0080] The PDMS film cured in Example 1 was taken out and plasma treated (air, 1 min). After being taken out, it was placed in a vacuum coating apparatus, 1.5 g of parylene was added, and the film was coated under vacuum conditions. After the coating was completed, it was taken out and stored. (No microstructure on the surface)

[0081] Example 5

[0082] The cured PDMS film in Example 1 was used as a low modulus surface, the microstructured parylene-PDMS sample in Example 2 was used as a modulus mismatch-microstructure surface (self-driven anti-icing material), the parylene-glass sample in Example 3 was used as a high modulus surface, and the parylene-PDMS sample in Example 4 was used as a modulus mismatch surface. The four samples were subjected to ice adhesion test for comparison. The experimental apparatus is as follows: Figure 5 The results are shown in Figure 6The results show that the modulus mismatch-microstructure surface can further reduce the ice adhesion strength (<10 kPa) compared with the modulus mismatch surface.

[0083] De-icing test specific steps:

[0084] (1) Use a clamp to fix the sample to be tested on the surface of the cold table, and introduce dry nitrogen to reduce the humidity to 40% or below;

[0085] (2) Place a through glass cuvette on the sample, fill it with water, and freeze it at the selected experimental temperature;

[0086] (3) After the ice is formed, the dynamometer pushes the ice at the selected propulsion speed and records the dynamic change and peak value of the force during the process (the maximum force required to remove the ice).

[0087] (4) Calculate the ice adhesion force and interfacial cavitation time of the sample (the time difference from the time the dynamometer starts to detect the force to the time the force becomes zero).

[0088] Note:

[0089] (1) During the test, the cold stage temperature was -20°C;

[0090] (2) The area of ​​the ice cube is 4.0 cm 2 ;

[0091] (3) The moving platform speed is 0.5 mm / s.

[0092] (4) The test results are usually 3-5 times, and the average value is taken.

[0093] Example 6

[0094] The sample obtained in Example 2 was used as a template. After fluorinating its surface, the PDMS monomer and the curing agent were mixed in a ratio of 10:1 to obtain a precursor. After stirring evenly, the mixture was placed in a vacuum oven to remove bubbles at room temperature. The precursor was poured into the template (the thickness was controlled by a silica gel plate), cured at 100°C for 12 hours, and demolded after curing to obtain a reverse template, which was stored.

[0095] Example 7

[0096] After fluorinating the surface of the reverse template obtained in Example 6, the PDMS monomer and the curing agent were mixed in a ratio of 50:1 to obtain a precursor, which was evenly stirred and placed in a vacuum oven to remove bubbles at room temperature. The precursor was poured into the template (the thickness was controlled by a silica gel plate), cured at 100°C for 12 hours, and demolded after curing to obtain a PDMS sample with a microstructure, which was stored.

[0097] Example 8

[0098] Take the parylene-PDMS with microstructure in Example 2 (self-driven anti-icing material), the parylene-PDMS without microstructure in Example 4, the PDMS sample in Example 1, and the PDMS sample with microstructure in Example 7 (Note: the PDMS curing ratio of the four samples is 50:1; the samples with microstructure size have the same structure size). The above four samples are divided into two groups: low modulus surface with / without structure (PDMS) and modulus mismatch surface (parylene-PDMS). The four are compared in ice adhesion test to verify the effect of microstructure on reducing adhesion strength. The results are as follows. Figure 7 As shown in the figure, the results prove that a single microstructure cannot achieve the purpose of reducing ice adhesion strength, but instead increases the adhesion strength by increasing the ice-solid contact area.

[0099] Example 9

[0100] The samples obtained in Example 2 and Example 4 were divided into 7 groups of samples (detailed information is as follows), with 3-5 parallel samples in each group, and deicing experiments were carried out (the specific steps of the deicing test are the same as those in Example 5).

[0101]

[0102] The results are as follows Figure 8 As shown in the figure, there is a synergistic effect between modulus mismatch and microstructure, which can further reduce the adhesion strength and further shorten the interfacial cavitation time. The degree of modulus mismatch can affect the adhesion strength and can be adjusted according to specific needs.

[0103] Example 10

[0104] The PDMS (50:1) samples in Example 1 were divided into 9 groups, each with 3-5 parallel samples, placed in a vacuum coating apparatus, and different amounts of parylene (as shown in the table below) were added to coat the samples under vacuum conditions. After coating, the samples were taken out and stored. The thickness corresponding to the different contents of parylene was measured by a thickness gauge (the results are shown in the table below). Fig. 9 As shown, the specific steps of the deicing test are the same as those of Example 5).

[0105]

[0106] The above samples were subjected to de-icing test. The de-icing test results of the above samples are shown in the attached Fig.10 .

[0107] Embodiment 11

[0108] Take the PDMS (50:1) sample in Example 1 and the microstructured parylene-PDMS (50:1) sample in Example 2 (self-driven anti-icing material). Fix the pre-made PMMA ice mold (19*19cm) on the sample, add water for in-situ freezing, and the freezing temperature is -20℃. After the freezing is completed, pick up the entire ice-covered sample, turn it over, and observe the self-detachment of the ice on the two surfaces. The results are as follows Fig.11 As shown, the ice on the microstructured parylene-PDMS (50:1) sample fell off quickly and automatically, while the ice on the surface of the PDMS (50:1) sample could not fall off by itself under the action of gravity.

[0109] Example 12

[0110] Take several pieces of parylene-PDMS (self-driven anti-icing material) with microstructures in Example 2, splice and fix them on an aluminum plate. A large area of ​​1.0*0.7m self-driven anti-icing material surface is obtained. Place the pre-made PMMA frozen ice mold (0.9*0.6m) on the sample surface, add water for in-situ freezing, and the freezing temperature is -10℃. After the freezing is completed, the entire ice-covered sample is vertically tilted slightly, and the ice falls off automatically. The results are as follows Fig.12 shown.

[0111] Example 13

[0112] After fluorinating the surface of the reverse template obtained in Example 6, the PDMS monomer and the curing agent were mixed in a ratio of 10:1 to obtain a precursor, which was evenly stirred and placed in a vacuum oven to remove bubbles at room temperature. The precursor was poured into the template (the thickness was controlled by a silica gel plate), cured at 100°C for 12 hours, and demolded after curing to obtain a PDMS (10:1) sample with a microstructure, which was stored.

[0113] Embodiment 14

[0114] The PDMS (10:1) with microstructure in Example 13 was used as a positive template, and the microstructure was replicated on a PMMA sheet by nanoimprinting to obtain a PMMA model with a reverse structure. The model was used to emboss polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride (PVDF) films. Save.

[0115] Embodiment 15

[0116] The bottom of the polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride (PVDF) film with microstructures obtained in Example 14 was coated with a silane coupling agent and placed at the bottom. The prepared silicone plate mold was fixed on the film and cast with the PDMS precursor that had been stirred evenly and de-bubbled (the thickness was controlled by the silicone plate). Curing was carried out at 60°C for 12 hours, and demolding was carried out after curing and storage.

[0117] Example 16

[0118] Take the three self-driving anti-icing materials obtained in Example 15 and the sample in Example 2 (Note: the selected samples have the same substrate modulus and microstructure size). In addition, take the sample in Example 3 and the surface of pure polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride (PVDF) materials. Divide into 4 groups, the specific materials are shown in the following table

[0119]

[0120] The above four groups of materials were tested for ice adhesion strength. The test results are as follows: Fig.13 The results show that the design principle of the self-driven anti-icing material is universal.

[0121] Embodiment 17

[0122] The parylene-PDMS (self-driven anti-icing material) with microstructure in Example 2 was divided into 3 groups, and the ice adhesion strength was tested 100 times respectively, and each result was the average of the results of the 3 samples. Fig.14 As shown, the specific steps of the deicing test are the same as those of Example 5).

[0123] Embodiment 18

[0124] The microstructured Parylene-PDMS (self-driven anti-icing material) in Example 2 was divided into 5 groups and iced by micro-droplets, static water, high humidity (93%), frost ice, and clear ice. The ice adhesion strength was tested and the results were as follows. Among them, the frost ice and clear ice conditions were completed in an icing wind tunnel, and the specific condition parameters were as follows Fig.15 , Fig.16 shown.

[0125] Embodiment 19

[0126] The parylene-PDMS (self-driven anti-icing material) with microstructures in Example 2 was divided into 5 groups, each group having 3 parallel samples. The freezing temperature of each group of samples was different, as shown in the following table.

[0127] Group No. 1 2 3 4 5 Temperature(℃) -10 -20 -30 -40 -50

[0128] The ice adhesion strength test was carried out on these samples. Fig.17 The results show that temperature has little effect on the material.

[0129] Embodiment 20

[0130] Take the PDMS sample in Example 1, immerse it in silicone oil for 1 week, then take it out to obtain an ultra-smooth surface, and store it.

[0131] Embodiment 21

[0132] Take the superslippery surface obtained in Example 20 and the parylene-PDMS surface with microstructures (self-driven anti-icing material) in Example 2, scatter dust on the surface of the material, and place the two material surfaces at an angle of 30 degrees to the ground. Then use a syringe filled with water to spray the surface with dust attached. The results are as follows: Fig.18 As shown in the figure, there is still dust adhering to the super-slip surface, and the dust on the surface of the self-driving anti-icing material is washed away by water, making it as clean as before.

[0133] Embodiment 22

[0134] Several microstructured parylene-PDMS surfaces (self-driven anti-icing materials) in Example 2 were placed in a salt spray machine, taken out after a period of treatment, tested for ice adhesion strength, and then placed in the salt spray machine again, and the cycle was repeated for 31 days. The results are shown in FIG. Fig.19 shown.

[0135] Embodiment 23

[0136] Several polyvinylidene fluoride-PDMS surfaces with microstructures (self-driven anti-icing materials) in Example 15 were placed in a UV aging machine. After being treated for 10 days, they were taken out and tested for ice adhesion strength. They were then placed in the machine again, and the cycle lasted for 30 days. The results are shown in Figure 2. Fig. 20 shown.

[0137] Embodiment 24

[0138] Several parylene-PDMS surfaces with microstructures (self-driven anti-icing materials) in Example 2 were taken and divided into three groups. 3M tape was adhered to the surfaces and then torn off. The cycle was repeated for 500 times, and the change in ice adhesion strength was recorded. The results are shown in FIG. Fig.21 shown.

[0139] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.

Claims

1. A fast self-driving anti-icing material and preparation method, characterized in that: A modulus mismatch structure comprising at least two materials, wherein the modulus span of the modulus mismatch structure is along the Z-axis direction or at a certain angle to the Z-axis; The surface of the fast self-driven anti-icing material has a synergistic effect of microstructure, modulus mismatch structure and surface microstructure.

2. The fast self-driving anti-icing material and preparation method according to claim 1, characterized in that: The modulus mismatch structure is a structure of high modulus material and low modulus material distributed along the Z-axis direction.

3. The fast self-driving anti-icing material and preparation method according to claim 1, characterized in that: The microstructure is micrometer-scale or nanometer-scale, continuous or discontinuous, isotropic or anisotropic folds, micropillars, grooves, fish-scale protrusions, inverted pyramids or inverted triangle protrusions.

4. The fast self-driving anti-icing material and preparation method according to claim 1, characterized in that: The modulus mismatch structure includes a first modulus material and a second modulus material. The elastic modulus of the first modulus material and the elastic modulus of the second modulus material are not equal, thereby forming a modulus fracture mutation of the first modulus material and the second modulus material in a certain direction.

5. The fast self-driving anti-icing material and preparation method according to claim 4, characterized in that: The difference between the elastic modulus of the first modulus material and the elastic modulus of the second modulus material is in the range of 0.04 MPa to 3.6 GPa.

6. The fast self-driving anti-icing material and preparation method according to claim 5, characterized in that: The first modulus material is a metal or metal oxide material, glass, a silicon substrate or a high molecular polymer organic material.

7. The method for preparing a fast self-driving anti-icing material according to claim 1, characterized in that: Step 1: preparing a substrate sheet or film material of a first modulus material, and preparing the substrate sheet or film material by spin coating, spray coating, casting, film laying, or roller coating the first modulus material with a lower modulus; Step 2: Prepare a second modulus material with a higher modulus in a manner that can cause thermal instability in the first modulus material; since the first modulus material is instability and deforms, when the applied conditions are removed, the two shrinkage mismatches due to different moduli lead to surface microstructures.

8. The preparation method according to claim 7, characterized in that: Step 1 includes: Step 11A: Making a template with a microstructure according to the designed pattern; Step 12A: injecting a precursor of the first modulus material into the mold, and forming a first modulus material substrate with a microstructure after curing and demoulding.

9. The preparation method according to claim 7, characterized in that: Step 2 also includes: Step 21: covering the second modulus material on the first modulus material substrate by deposition, spraying or film laying.

10. The preparation method according to claim 7, characterized in that: Step 1 also includes: Step 11B: Making a template with a microstructure according to the designed pattern; Step 12B: forming a microstructure on the first modulus material film by hot embossing.

Citation Information

Cited By

  • Polar region self-deicing anticorrosive coating and preparation method thereof

    CN120137483A

  • Temperature response type bionic anti-scaling coating and preparation method thereof

    CN120718540A

  • Temperature-responsive biomimetic antifouling coating and preparation method thereof

    CN120718540B